PENGERTIAN MUQOBALAH DAN CONTOHNYA (MUQOBALAH DALAM AL-QUR’AN) - Fikri Alfarizi; Fikri Kholis Pratama (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2026)
This study aims to examine the concept of Muqobalah, its examples, and its application in the verses of the Qur’an. Muqobalah is one of the branches of Badi’ in Arabic rhetoric (Balaghah) that involves presenting several meanings followed by their corresponding opposites in a systematic order to strengthen meaning and enhance linguistic beauty. This research employs a library research method with a descriptive qualitative approach. The data were collected from the Qur’an, classical and contemporary Qur’anic commentaries (tafsir), books on Balaghah, scholarly journals, and other relevant literature related to the study of Muqobalah. The findings reveal that Muqobalah plays a significant role in the Qur’an as one of the manifestations of its linguistic miracle, functioning to clarify meanings, emphasize messages, and provide educational as well as persuasive effects on readers. Forms of Muqobalah are widely found in verses discussing contrasts such as faith and disbelief, good and evil, paradise and hell, as well as guidance and misguidance. The use of Muqobalah in the Qur’an not only contributes to its aesthetic excellence but also helps readers understand the consequences of their actions and life choices. Furthermore, Muqobalah contains various wisdoms, including the cultivation of moral values, the strengthening of faith, the development of reflective thinking, and the enhancement of understanding of the Qur’anic message. Therefore, the study of Muqobalah is essential for appreciating the linguistic beauty of the Qur’an and for gaining a deeper understanding of its teachings and messages.